1
$\begingroup$

How would I go about factoring $$x^4-x^2-12=0$$

I'm supposed to find the roots of this without the use of calculators (well we do have TI's but some don't so I suppose they're assuming we can solve this manually). But I can't see how I'd factor this simply?

$\endgroup$
3
  • $\begingroup$ As an intermediate step, write it as a polynomial in $y = x^2$. $\endgroup$ Apr 13 '14 at 18:41
  • $\begingroup$ Sorry, I don't understand what you mean? Do you mean I write it as: $$x^2 = x^4-12$$? $\endgroup$ Apr 13 '14 at 18:42
  • 1
    $\begingroup$ No, $y^2-y-12$. $\endgroup$ Apr 13 '14 at 18:44
8
$\begingroup$

Let $t=x^2$, then you have $t^2-t-12=0$ which is a lot easier to factor. Once you're done that, resubstitute $x^2$ back in.

$\endgroup$
3
$\begingroup$

Write $y=x^2$, giving $y^2-y-12=0=(x^2+3)(x^2-4)$. I'll leave the steps in the factorization of the quadratic $y^2-y-12=0$ to you.

$\endgroup$
2
  • $\begingroup$ Ah right, that's how you did it. I thought I had to pull $12$ down by a factor of $x^2$ as well for some reason. $\endgroup$ Apr 13 '14 at 18:43
  • $\begingroup$ @user3200098 No, doing that would be redundant and wrong. $\endgroup$
    – user122283
    Apr 13 '14 at 18:44
2
$\begingroup$

Change the variable so you have $y=x^2$ and so solve for $$y^2 - y -12 =0$$

You will find $y = -3$ or $y = 4$, then solve $x^2 = -3$ and $x^2 = 4$. You will have multiple roots which are $$x_1 = -2$$

$$x_2 = 2 $$ $$x_3 = -i\sqrt{3} $$ $$x_4 = i\sqrt{3} $$

You will end up with

$$ x^4 - x^2 -12 = (x-2)(x+2)(x-i\sqrt{3})(x+i\sqrt{3}) $$

Forget $x_3$ and $x_4$ if you are in $\mathbb{R} $ :

$$ x^4 - x^2 -12 = (x-2)(x+2)(x^2+3) $$

$\endgroup$
0
$\begingroup$

Let $t=x^2$

Now we have

$t^2-t-12=0 $

$\Delta=1+48=49$

$t_1=-3$, $t_2=4$

go back to x

$x_1=\sqrt-3$, $x_2=-\sqrt-3$, $x_3=2$, $x_4=-2$

If you had complex numbers in school, you can easily compute that $x_1=i\sqrt3$ and $x_2=-i\sqrt3$

If not, just write that there are no real roots of negative numbers.

$\endgroup$
0
$\begingroup$

Note that $x^4 - x^2 -12 = (x^2 - 4)(x^2 + 3)$; this factorization was guesswork on my part, based on the observation that $(x^2 - \mu_1)(x^2 - \mu_2) = x^4 - (\mu_1 + \mu_2)x^2 + \mu_1 \mu_2$; so I looked for integers $\mu_1$, $\mu_2$ such that $\mu_1 + \mu_2 = 1$ and $\mu_1 \mu_2 = -12$; it was easy to make such a guess. But this factorization could have been done systematically by setting $y = x^2$, as several others have suggested, and then realizing the roots of the quadratic $y^2 - y -12 = 0$ are $4, -3$; this of course can be done with aid of the quadratic formula. Once we have $x^4 - x^2 -12 = (x^2 - 4)(x^2 + 3)$, we can factor further by using $x^2 - 4 = (x + 2)(x - 2)$; thus $x^4 - x^2 -12 = (x + 2)(x - 2)(x^2 + 3)$; we can't go further over the reals since $x^2 + 3$ has no real zeroes.

That's how I'd do it, in any event.

Hope this helps. Cheerio,

and as always,

Fiat Lux!!!

$\endgroup$
0
$\begingroup$

This "quartic" equation is actually a quadratic in $x^2$. Notice that $$x^4 - x^2 - 12 \equiv \left(x^2\right)^2 - \left(x^2\right) - 12$$ If we re-name $x^2$ as $u$ then we have $$x^4 - x^2 - 12 = 0 \iff u^2 - u - 12 = 0$$ We are able to factorise $u^2-u-12$. Indeed $u^2-u-12 \equiv (u+3)(u-4)$. It follows that $$u^2-u-12=0 \iff u=-3,\, 4$$ Since $u$ is used in place of $x^2$ we have $x^2=-3, \, 4$. It follows that $$x^4-x^2-12=0 \iff x = \pm\mathrm{i}\sqrt{3}, \, \pm 2$$ If you are working over the real numbers then $x= \pm 2$ are the only valid solutions.

$\endgroup$
0
$\begingroup$

$$x^4-x^2-12=0\,\,\text{can be written as: }\color{blue}{(x^2)}^2-\color{blue}{(x^2)}-12=0.$$ which with a change of variable is a quadratic equation, that can be solved using the quadratic formula to get: $$x^2=\dfrac{1\pm\sqrt{1+4\cdot12}}{2}.$$ And so, you will get $2$ roots, and recall that: If $\alpha$ is a root of $\mathrm P(x)$, then there exist one polynomial $\mathrm Q(x)$ such that $\mathrm P(x)=(x-\alpha)\cdot\mathrm Q(x)$ and so you'll have to use polynomial long division.

After doing all of those steps, you will find that: $$x^4-x^2-12=(x-2 ) (2 + x) (3 + x^2).$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.